Cascade morphology transition in bcc metals. (18th May 2015) - Setyawan, Wahyu; Selby, Aaron P; Juslin, Niklas; Stoller, Roger E; Wirth, Brian D; Kurtz, Richard J
Abstract: Energetic atom collisions in solids induce shockwaves with complex morphologies. In this paper, we establish the existence of a morphological transition in such cascades. The order parameter of the morphology is defined as the exponent, b, in the defect production curve as a function of cascade energy . Response of different bcc metals can be compared in a consistent energy domain when the energy is normalized by the transition energy, μ, between the high- and the low-energy regime. Using Cr, Fe, Mo and W data, an empirical formula of μ as a function of displacement threshold energy, E d, is presented for bcc metals.